Transitional Cell Carcinoma of the Upper Ureter Metastatic to the Thoracic Spine Presenting as a Spinal Cord Compression. (2008) - Larkin, J. O.; Cullen, I. M.; Kelleher, M. O.; Fitzgibbon, J.; Keohane, K.; O'Sullivan, M. G. J.; Rogers, E.
Abstract : We performed a left nephroureterectomy for a gentleman with transitional cell carcinoma of the upper ureter. Histological analysis revealed it to be a T1 lesion, but to be highly mitotically active. The gentleman defaulted on adjuvant therapy and defaulted on follow-up. He represented with symptoms of acute spinal cord compression and magnetic resonance imaging demonstrated a lesion at T6/7. Neurosurgical resection of the lesion showed it to be a metastatic deposit from the ureteric primary. Despite surgical debulking and subsequent radiotherapy to the lesion, the patient died secondary to metastatic complications. This case report is of interest to the surgeon as it demonstrates both the high metastatic potential of upper tract carcinomas and educates the surgeon on the presentation of acute spinal cord compression.